Outcome of Robotic Surgery for Endometrial Cancer as a Function of Patient Age. Issue 4 (May 2015) - Zeng, Xing Ziggy; Lavoue, Vincent; Lau, Susie; Press, Joshua Z.; Abitbol, Jeremie; Gotlieb, Raphael; How, Jeffrey; Wang, Yifan; Gotlieb, Walter H.
<x xml:space="preserve">Abstract</x> Objective This study aimed to evaluate and compare robot-assisted surgical staging on clinical outcomes, including quality of life and survival, as a function of patient age. Methods Evaluation and comparison of perioperative morbidity, survival, and postoperative quality of life after prospective accumulation of clinical information including outcome measures for patients with endometrial cancer during the first 5 years of a robotic program, based on the following 3 age categories: women older than 80 years, women between 70 and 80 years, and women younger than 70 years. Results All consecutive patients with endometrial cancer undergoing robotic surgery (n = 303) were included, with 197 women younger than 70 years, 75 women between 70 and 80 years, and 31 women older than 80 years. There were significantly more patients with advanced stage (stage II to IV in 17%, 34%, and 35%, P = 0.02) and grade 3 disease (26%, 43%, and 58%, P = 0.002) with increasing age. The perioperative data showed similar grade I or II complications (Clavien-Dindo classification) between the groups, but significantly more grade III and IV complications for women older than 80 years compared with women 80 years or younger (10% vs 1%, P = 0.004). The time needed to resume chore activities was significantly shorter for patients 70 years or older than patients younger than 70 years [8.9 (8.7) vs 18.8 (25.5) days, P = 0.048]. Overall, all patients irrespective of age were highly satisfied with the procedure. There was no difference between young and elderly patients for disease-free survival (P = 0.99). Conclusions Patient's age did not influence minor postoperative morbidity or overall satisfaction after robotic assisted surgery for endometrial cancer. Elderly patients had more major postoperative morbidity but resumed activities quicker than younger patients.